Proposed constants for Bieniawski’s strength criterion for rocks and coal - Bineshian, Hossein; Rasouli, Vamegh; Ghazvinian, Abdolhadi; Bineshian, Zahra (IJRSG, 2013)
Bieniawski’s strength criterion is one of the most widely used criteria for strength estimation of intact rocks. This criterion, however, only considers compression loading. In Bieniawski’s criterion rocks are distinguished in their properties using two parameters В and a. Selecting these parameters, through lab experiments, as representative as possible for a certain type of rock is significantly important. The quality of lab tests, the number of tests and statistical approaches used to estimate these parameters are some of the important factors, which can influence the accuracy of the estimation. Several attempts have been made by different researchers to propose these parameters for different rock types in different regions. In this paper a similar attempt was made to determine more representative constants for Bieniawski’s criterion. This work is different from past studies in that we have based our analysis on a very large number of lab experimental data gathered from the literature and some carried out for the purpose of this study. The studied data includes a wide range of rock types from soft to hard including sandstones, shales and coals. Both linear conversion and nonlinear regression models were applied to the lab data and as a result Bieniawski’s constants were proposed for each rock type. For coal, the results are presented as a function of the loading angle with respect to the coal’s fractures. The results of nonlinear models were found to be associated with higher correlation coefficients. Also a correlation between parameter В and unconfined compressive strength was proposed. The results of this study were also compared with similar work presented in the past.